Effects of temperature on methanol adsorption on functionalized graphite: Saturation of functional groups - Waralee Dilokekunakul (2019)
© 2018 Grand Canonical Monte Carlo simulation of methanol adsorption on a graphite model with two hydroxyl groups grafted on the surface has been carried out to investigate the effects of temperature in the range of 278-360 K. The spacing between the OH groups was chosen so that two hydrogen bonds could be formed with the first methanol molecule. In the Henry law region, the isosteric heat at zero loading is greater than the condensation heat. When the loading is increased, the isosteric heat at low temperatures decreases slightly and exhibits a shoulder, which is associated with the formation of a cluster of methanol molecules around one OH group. On further increase in loading, the adsorbate-adsorbate interactions decrease because methanol begins to adsorb on the other OH group, resulting in a sharp decrease in the isosteric heat to a minimum, at which point both OH groups are covered with methanol molecules. At higher temperatures the isosteric heat at zero loading decreases but remains higher than the condensation heat. The shoulder heat is progressively diminished with temperature because methanol molecules are distributed over the two OH groups, due to the entropic effects. Interestingly, the minimum heat still occurs when the functional groups are covered and is even more pronounced at high temperatures.